Religious Moderation Villages and Interreligious Tolerance: Implementation, Successes, and Challenges in Pamekasan, Indonesia - Haqqullah, Moh. Wasil; Harisah, Harisah (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2025)
This study aims to explore the implementation of religious moderation through the establishment of Religious Moderation Villages (Kampung Moderasi Beragama/KMB) as a strategy to address religious conflicts and enhance inter-religious tolerance in Pamekasan Regency, East Java. Employing a qualitative approach, the study combines in-depth interviews and literature reviews. Informants were purposively selected from local government officials, administrators of KMB programs, and prominent religious leaders with direct involvement and extensive knowledge regarding the practice of religious moderation. Data analysis followed the thematic analysis framework by Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The findings reveal that the implementation of KMB has effectively strengthened tolerance among religious groups, evidenced by decreased occurrences of internal and inter-religious conflicts within the study area. Key indicators of successful religious moderation include enhanced harmonious social interactions among diverse religious communities, decreased resistance toward religious differences, and increased collective awareness of the importance of moderate religious attitudes. Nonetheless, the study identifies ongoing challenges, notably persistent extremist paradigms held by certain religious organizations, insufficient community education on religious moderation values, and limited structural support from local governmental institutions. The study recommends enhancing synergy among local governments, religious leaders, and community members to consistently educate society about moderation values, thus achieving sustainable social harmony in Pamekasan Regency.